As propriedades do solo e o desmoronamento de fossas em Marechal Cândido Rondon - PR - Rupolo, Edimara Lucia (2008)
The knowledge of the physic-hidrics and mechanical characteristics of the pedological covering can help the understanding and behaviouring of the physical environment. The behaviouring of the pedologic material can interfere significantly in the developing of various processes that diminish the physical environment and generates cost either to the public power and the community in general. In the city of Marechal Candido Rondon/PR, the reduction of the black pits, that retain the domestic sewers, has been done since the sewerage system doesn't collect the whole urban mesh. This study aims to verify the relationship between the soil properties and the sewage collapse in Marechal Candido Rondon, where nine surveys were done as well as the opening of three trenches in a representative slope of the urban mesh topography of the city. The analyzed samples showed that the soils are well developed. A red Eutroferic Latosol was identified in the average high slope, and another one in the inferior third and a Cambisol Haplic Eutroferic in the base of the slope. Those soils are higly porosity of argillaceous texture to high argillaceous with a high saturation in the basis, a low capacity of cationic change and good absortion capacity of the liquid effluents and predominance of high index of erodibility in the horizons with a microaggregate structure. The properties of the soil identified they showed a fragility in the horizon Bw, that together with the form of use of the soil they aren't responsible for the black pit's collapse.